Oxidative Stress as a Reliable Biomarker of Carotid Plaque Instability: A Pilot Study - Norbert Svoboda; Karolina Kočí; Anna Seidlová; Václav Mandys; Jiří Suttnar; Alžběta Hlaváčková; Ondřej Kučerka; David Netuka; Martin Malý (MDPI AG, 2023)
Background: Predicting stroke risk in patients with carotid artery stenosis (CS) remains challenging. Circulating biomarkers seem to provide improvements with respect to risk stratification. Methods: Study patients who underwent carotid endarterectomy were categorized into four groups according to symptomatology and compared as follows: symptomatic with asymptomatic patients; and asymptomatic patients including amaurosis fugax (AF) (asymptomatic + AF group) with patients with a transient ischemic attack (TIA) or brain stroke (BS) (hemispheric brain stroke group). Carotid specimens were histologically analyzed and classified based on the American Heart Classification (AHA) standard. As a marker of OS, the plasma levels of malondialdehyde (MDA) were measured. Comparisons of MDA plasma levels between groups were analyzed. Results: In total, 35 patients were included in the study. There were 22 (63%) patients in the asymptomatic group and 13 (37%) in the symptomatic group. Atheromatous plaque (p = 0.03) and old hemorrhage (p = 0.05), fibrous plaque (p = 0.04), myxoid changes (p = 0.02), plaques without hemorrhage (p = 0.04), significant neovascularization (p = 0.04) and AHA classification (p = 0.006) had significant correlations with clinical presentation. There were 26 (74%) patients in the asymptomatic group and 9 (26%) in the hemispheric brain stroke group. Atheromatous plaque (p = 0.02), old hemorrhage (p = 0.05) and plaques without neovascularization (p = 0.02), fibrous plaque (p = 0.03), plaques without hemorrhage (p = 0.02) and AHA classification (p = 0.01) had significant correlations with clinical presentation. There was no significant difference between symptomatic and asymptomatic groups with respect to MDA plasma levels (p = 0.232). A significant difference was observed when MDA plasma levels were compared to asymptomatic + AF and the hemispheric stroke group (p = 0.002). Conclusions: MDA plasma level correlates with the risk of hemispheric stroke (TIA or BS) and is a reliable marker of plaque vulnerability in carotid artery stenosis.